Advancing Metal-Air Battery Efficiency: MnO₂ Electrocatalyst Synthesized via Electrochemical Method - Giska Koesumasari Putri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates the effect of electrode quantity and voltage on MnO₂ nanoparticle yield and characteristics under acidic and basic conditions, while also evaluating MnO₂'s potential as an electrocatalyst in metal-air batteries. Methodology: Synthesis of MnO₂ was carried out by electrolysis of KMnO₄ solution with stirring using a magnetic stirrer. In acidic conditions, H₂SO₄ was used and the electrolysis process lasted for 30 minutes, while in basic conditions, 0.1 M KOH was used up to pH 9 and electrolysis for 24 hours. The research variables included voltage (2V and 4V) and the number of carbon electrodes (1 pair and 4 pairs). The electrolysis results were separated using a centrifuge, washed with demineralized water, and dried in a furnace. Main Findings: MnO₂ from electrolysis in acidic conditions tends to have a low crystalline structure, while in basic conditions it is amorphous with a larger surface area. The addition of electrodes and voltage reduces the surface area and increases particle agglomeration. Cyclic voltammetry tests show the ability of MnO₂ to reduce O₂ at all variables, in accordance with the standard oxygen reduction potential. Linear polarization tests show that MnO₂ synthesized in acidic conditions has better electrocatalytic activity than that synthesized in basic conditions. Novelty/Originality of this study: This study contributes data on the effect of electrolysis parameters on the yield and characteristics of MnO₂ as an electrocatalyst, and shows the best synthesis conditions for application in metal-air batteries.